The role of non governmental organizations in monitoring and evaluating public policies, measuring the effects stressing the impact on regional economic policy implementation - Judeu, Viorina (Studies and Scientific Researches. Economics Edition, 2010)
Regional policy implementation encounters difficulties and limitations similar to those for other areas of economic policy. The main difficulties are those arising from uncertainty in the gaps of time and the nature of the political climate. As a variant influencing the selection process by which a public interest issue to be solved and the stages of monitoring / evaluation of the implementation of public policies are often part of the current work of NGOs. Depending on the area of expertise / interest for a particular topic at a time, NGOs have chosen to monitor / assess the performance of authorities in implementing a solution to solve a problem, depending on certain parameters.